2014
DOI: 10.1177/1462474514527149
|View full text |Cite
|
Sign up to set email alerts
|

‘A culture of sharing’: Drug exchange in a Norwegian prison

Abstract: Despite growing numbers of drug users in prisons all over the western world, drug exchange behind bars has received little scholarly attention. The few studies that exist describe the prison drug economy as mainly following market-based principles of exchange. However, ethnographic fieldwork in a closed Norwegian prison reveals something different: prisoners share their drugs, rather than selling them. In this article, I describe and try to explain this ‘culture of sharing’. Drawing on anthropological theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 24 publications
2
46
1
4
Order By: Relevance
“…Contrary to other accounts in the literature, who portray prison drug use as individual acts and prison drug users as quite isolated in the prisoner community (e.g. Crewe 2005Crewe , 2009, I found that drug use in Kollen prison had a distinct social character, and that it had important inclusionary and exclusionary functions (see also Mjåland, 2014).…”
Section: Drug Use and Communitycontrasting
confidence: 43%
See 2 more Smart Citations
“…Contrary to other accounts in the literature, who portray prison drug use as individual acts and prison drug users as quite isolated in the prisoner community (e.g. Crewe 2005Crewe , 2009, I found that drug use in Kollen prison had a distinct social character, and that it had important inclusionary and exclusionary functions (see also Mjåland, 2014).…”
Section: Drug Use and Communitycontrasting
confidence: 43%
“…Contrary to the few other studies that are published on prison drug markets (e.g. Crewe, 2005Crewe, , 2009Penfold et al, 2005), drug exchange in Kollen prison did not follow market-based principles, but was rather organised as a gift-economy, where prisoners shared their drugs with vaguely stated expectations of receiving something in return in the future (Mjåland, 2014). A shared norm of reciprocating drug gifts made this form of exchange effective, and the stable supply of buprenorphine diverted from the dispensing of OMT helped produce a vibrant drug subculture in the prison.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…If inmates are running late on their return, "they can telephone ahead and a meal will be left out for them" (Pratt 2008, 122-123 When inmates desire contraband, they do not always rely on markets. Mjåland's (2014) observational and interview-based study (n=23 inmates; n=12 staff members) of illicit drug use at Norway's Kollen prison reveals that inmates get drugs through reciprocal sharing arrangements. One resident summarizes the relationship: "you have to give in order to get" (Mjåland 2014, 343).…”
Section: Inmates Govern Less When Officials Govern Wellmentioning
confidence: 99%
“…Crewe (2005Crewe ( , 2006, for instance, has shown that drug use and dealing tend to accentuate existing inequalities in prisons between powerful and more vulnerable prisoners, and also contribute to the prison becoming a low trust environment. Although less antagonistic cultures of (drug) sharing within prisons have also been documented (Mjåland, 2014;see also: Sandøy, 2015). Drug supply and dealing in prisons are therefore understood as more than simply economic activities.…”
mentioning
confidence: 99%